Sosialisasi dan Training Refresher pada 8 SPBU di Kota Semarang untuk Peningkatan Kualitas Pelayanan dan SOP - Deewar Mahesa; Sukardi Sukardi; Puji Setya Sunarka; Ribut Musprihadi; Nur Atiqa Yuniarti; Heru Eko Prasetyo; Camilus Isidorus Ikut; Ryan Arya Pramudya (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aimed to enhance the safety compliance and service quality of gas station (SPBU) operators in Semarang through a structured refresher training initiative. The training was conducted over eight days and involved 120 participants from eight different SPBU locations. The program adopted a comprehensive approach by combining theoretical sessions, practical simulations, and role-playing exercises tailored to address real-world scenarios faced by SPBU personnel. Key training components included emergency response protocols, customer service excellence, complaint management, and adherence to safety procedures. The outcomes of the program showed measurable improvements. Post-training evaluations revealed a significant increase in participants’ knowledge and understanding of operational safety and service standards. Additionally, a notable reduction in emergency response times was observed during simulated drills. Feedback collected from the participants indicated enhanced confidence in handling routine operations, responding to customer complaints, and executing emergency procedures. This reflects the program’s success in not only increasing technical competence but also in boosting the professional demeanor of SPBU staff. Despite its success, the program encountered challenges, particularly in aligning the training schedule with participants’ daily work commitments, which occasionally hindered full attendance. To ensure long-term impact and continuity, the program recommends implementing annual refresher training sessions in collaboration with local safety and regulatory authorities. This would foster a culture of continuous improvement and compliance among SPBU operators, ultimately contributing to safer and more efficient fuel service operations in the region. Overall, the initiative highlights the critical role of ongoing professional development in enhancing service delivery and maintaining high safety standards in the fuel retail sector.